2019 6th International Conference on Behavioral, Economic and Socio-Cultural Computing (BESC) 2019
DOI: 10.1109/besc48373.2019.8963036
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination on Social Networks: Types and Triggers

Abstract: Procrastination refers to a voluntary delay of a needed or committed task that might hurt productivity and wellbeing requirements such as self-acceptance, personal growth and positive relations with others. People might procrastinate due to a lack of motivation towards performing a task or a mismatch between the task and their skills. Social Networks Sites (SNS) are designed to provide users with the opportunity to socialise and feel relatedness despite being physically separated. SNSs design is typically equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 28 publications
(26 reference statements)
2
21
0
Order By: Relevance
“…Therefore, the distracting notification can be considered an external factor that could invoke and facilitate procrastination. Moreover, the design features of social networking sites (SNS) could facilitate procrastination in numerous cases such as users who instantly reply to messages to develop a positive self-image or because of the fear of missing out [ 7 , 8 ]. It has been suggested that procrastination is a trait that is determined by underlying personality factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the distracting notification can be considered an external factor that could invoke and facilitate procrastination. Moreover, the design features of social networking sites (SNS) could facilitate procrastination in numerous cases such as users who instantly reply to messages to develop a positive self-image or because of the fear of missing out [ 7 , 8 ]. It has been suggested that procrastination is a trait that is determined by underlying personality factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conflict could be argued to be one of the defining characteristics of procrastination in the context of SNS, as it means delaying one task in favour of staying on social media and doing something else [ 11 ]. This may be interconnected with digital addiction, where the desire to achieve mood modification leads individuals to use social media as a way to avoid stressful or demanding tasks [ 8 ]. Procrastination means a delay of another task and our previous research in [ 8 , 12 , 13 ] showed that users wish to see motivational elements in that task that then add a degree of satisfaction that they get from social media, for example, being rewarded, task completion and getting social support while doing it.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations